Процедурна генерація ландшафтів для мультимедійних застосунків - Стрюк, Д. С. (ХНУРЕ, 2025)
This article explores the advantages and challenges of using procedural generation techniques for landscape modeling in multimedia applications. It discusses improvements in visual realism, computational efficiency, and adaptability of terrain generation algorithms, as well as challenges related to performance optimization and integration with real-time rendering systems. Special attention is given to the balance between realism and computational efficiency in modern applications.
Keywords: процедурна генерація; ландшафт; мультимедійний застосунок